Survey on cooperative fusion technologies with perception, communication and control coupled in industrial Internet - Hui TIAN; Shuo HE; Shangjing LIN; Shaoshuai FAN; Gaofeng NIE; Xiurong JIANG (Tongxin xuebao)
The cooperative fusion with perception, communication and control is the inevitable trend of industrial Internet.Sorting out the research development and challenges of the cooperative fusion technologies with perception, communication and control in industrial Internet is of great significance to promote the development of industrial Internet.Firstly, the complicated coupling relationship among perception, communication and control in industrial Internet was introduced.Then, the related works and open problems of the cooperative fusion technologies with perception, communication and control were summarized.Finally, the future research directions were summarized and prospected for the problems of the cooperative fusion technologies with perception, communication and control in industrial Internet.